Analysis of the Caspian Sea within the framework of geopolitical theories (Journal of Oriental Studies, 2018)
This paper provides geopolitical views on the Caspian Sea. There is also analysis of western classicalgeopolitical works. The works of scientists who have not eliminated their relevance and haveplayed a role in geopolitics are now the most prominent works leading western foreign policy. Thegeographical scope of the Caspian Sea and its region is important in the international arena. Theenergy strategies of countries that have access to the energy-rich sea and its region have also beenanalyzed. The geopolitical landscape of the Cold War, especially geopolitical scholars, has continuedwith ideological theories.